EFFECT OF SHELLFISH PROTEIN HYDROLYSATE (SPH) OF PEARL OYSTER MEAT ON THE STATE OF WATER AND DENATURATION OF MYOFIBRILS DURING DEHYDRATION PROCESS - YS. Darmanto (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Pearl oyster meat, considered as the waste product of pearl industry, can be transformed to a useful product troght hydrolysis using protease enzyme. Protein hydrolysate of pearl oyster meat (SPH) was added to myofibrils (Mf) from lizard fish at certain ratios 2.5 – 12.5 g/100 gr Mf, and the changes in the state of water in myofibrils associated with dehydration were analyzed on the basis a water sorption isotherm curve and isosteric sorption heat. Involvement of these change denaturation of myofibrils was investigated with respect to Ca-ATPase activity. The addition of SPH resulted a decreased of water activity, an increase in the amount of monolayer or multilayer water and increase in the isosteric sorption heat, indicative the changes in the state of water in myofibrils. Furthermore, it wa found that SPH has suppressive effects on the denaturation of myofibrils during dehydration process.